Fusarium Species Causing Dry Rot of Carrot in Central Argentina - Favaro, María Alejandra; Maumary, Roxana Lorena; Lutz, Alejandra Liliana; Soressi, Marcelo Carlos; Del Valle, Eleodoro Eduardo; Fernandez, Laura Noemí (Wiley, 2024)
Carrot (Daucus carota L. subsp. sativus) cultivation is important in Argentina, with the Garay department in Santa Fe province being a key production area. In recent years, dry rot symptoms have afflicted various carrot cultivars, resulting in substantial field losses and postharvest discards. Several soilborne pathogens, including Fusarium species, have been implicated in similar carrot diseases globally. This study aimed to identify the specific causal agent responsible for dry rot in carrots in central Argentina to enable targeted disease management strategies. Samples of symptomatic carrots were collected from fields in the Garay department. Fungal isolates were obtained from the infected tissue and subjected to morphological and molecular analyses. Pathogenicity tests were conducted to confirm the ability of the isolates to cause disease symptoms in carrots. Based on morphological and molecular identification, isolates were identified as Fusarium nirenbergiae, Fusarium triseptatum and Fusarium solani. Pathogenicity tests demonstrated that the three Fusarium species were capable of causing dry rot symptoms in carrots. This study represents the first report of Fusarium nirenbergiae, Fusarium triseptatum and Fusarium solani causing dry rot in carrots in Argentina.